2014
DOI: 10.1515/hsz-2014-0195
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of hematopoiesis: the PU.1 chromatin connection

Abstract: Purine-rich box1 (PU.1) is a transcription factor that not only has a key role in the development of most hematopoietic cell lineages but also in the suppression of leukemia. To exert these functions, PU.1 can cross-talk with multiple different proteins by forming complexes in order to activate or repress transcription. Among its protein partners are chromatin remodelers, DNA methyltransferases, and a number of other transcription factors with important roles in hematopoiesis. While a great deal of knowledge h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 87 publications
4
24
0
Order By: Relevance
“…SPI1 (PU.1) is found by SPEID to be a corresponding motif feature with top 5% feature importance in promoter regions. Studies have revealed the important role of SPI1 in gene regulation [35,36]. These results demonstrate the potential of SPEID in identifying important TF motif sequences involved in EPI without using any known TF motif information.…”
Section: Evaluating the Importance Of Known Sequence Features Using Isupporting
confidence: 54%
“…SPI1 (PU.1) is found by SPEID to be a corresponding motif feature with top 5% feature importance in promoter regions. Studies have revealed the important role of SPI1 in gene regulation [35,36]. These results demonstrate the potential of SPEID in identifying important TF motif sequences involved in EPI without using any known TF motif information.…”
Section: Evaluating the Importance Of Known Sequence Features Using Isupporting
confidence: 54%
“…We identified several other proteins with poor univariate importance that nonetheless have known roles in chromatin looping and were highly ranked by TargetFinder. These include SP1 57,58 , SPI1 (PU.1) 59,60 , HCFC1 which co-localizes with looping factor ZNF143 42 , and TBP whose TAF3 subunit is recruited by CTCF to distal promoters 61 and which is linked with long range interactions 62 . Finally, WHSC1 (NSD2) is a histone methyltransferase of H3K36me3 and therefore is associated with predictive marks of elongation 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The established molecular pathophysiology associated with some of these mechanisms are listed. The literature on ETS proteins is vast and this summary is only intended to be illustrative; readers interested in specific aspects or paralogs mentioned in this figure are referred to reviews and studies such as the following: 26,49,51,53,66,[87][88][89][90][91][92][93] Note that auto-inhibition (indicated by the cartoon helix) is not a universal feature of ETS proteins; several paralogs, such as PU.1, are not auto-inhibited. Abbreviations: AML, acute myeloid leukemia; Ca, cancer; cHD, classical Hodgkin's disease; MM, multiple myeloma.…”
Section: Role Of Molecular Hydration In Dna Recognition By Ets Proteinsmentioning
confidence: 99%
“…While the importance of epigenetic regulation of ETSdependent transcription is well established in hematopoiesis and cancer, 55,[66][67][68] the mechanisms by which ETS activity are modulated at epigenetically modified DNA, with or without nucleosome, are not well understood. Genomic surveys have found that hematopoietic ETS transcription factors are over-represented in hypermethylated regions.…”
Section: Differential Tolerance To Cpg Methylationmentioning
confidence: 99%